Multi-Level Simulation for Dynamic Analysis of A Domestic Electric oven in Forced Convective Heating—Evaluation and Optimization of Energy Consumption Using the Brick Test (Future Cities and Environment, 2025)
The study proposes a novel method aimed at the optimization of the energy consumption of a domestic electric oven. The goal is to achieve the best trade-off between the oven energy consumption and its performance in terms of thermal distribution. The method revolves around a multi-level analysis that couples detailed, steady-state CFD results with the transient evaluation of the associated lumped parameters. In particular, the distribution of the heat transfer coefficients (convective and radiative) is computed through the CFD analysis and used as the input for the dynamic analysis to get the time evolution of the oven energy consumption. The tested oven has a volume of 68L and is equipped with three heating elements. The numerical model has been validated through measurement data on the temperature distribution, showing high accuracy in predicting the thermal behaviour and energy fluxes of the cavity. Moreover, experimental validation of the energy consumption has been performed following the EN 60350 standard, which involves a wet brick initially cooled to 5 ± 2 °C and then heated until its core temperature rises by 55 °C. Results suggest that this approach can lead to a substantial reduction of the oven energy consumption while maintaining high performance standards.